GE_GERICHTE C/1020/2015 vom 30. August 2017 - GE Cour de justice (2017)
DIVORCE ; MESURE PROVISIONNELLE ; MODIFICATION DES CIRCONSTANCES ; OBLIGATION D'ENTRETIEN ; CONJOINT ; ENFANT ; MAJORITÉ(ÂGE) | CPC.276; CC.285;